PENGARUH KUALITAS PELAPORAN KEUANGAN, JATUH TEMPO UTANG, DAN KUALITAS LABA AKUNTANSI TERHADAP EFISIENSI INVESTASI PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rinda Nurfita; Ferdila Ferdila; Baru Harahap; Andi Auliya Ramadhany; Khadijah Khadijah (LPPM Universitas Putera Batam, 2026)
This study looks at how financial reporting quality, the length of time companies take to repay their debts, and the reliability of their earnings reports affect how efficiently they make investments in transportation and logistics firms listed on the Indonesia Stock Exchange from 2020 to 2024. The study looks at how a company's internal financial data and the way it manages its debt affect how well its investment decisions work. The goal of this research is to look at how these variables affect investment efficiency, both on their own and when considered together. A quantitative method was used, which involved multiple linear regression analysis, based on financial statement data gathered through documentation methods. The findings indicate that higher quality in financial reporting is linked to lower investment efficiency, and longer debt maturity also has a negative impact. However, the quality of accounting earnings does not have a meaningful effect on investment efficiency. At the same time, the three variables have a big impact on how efficiently investments work. The results show that even though these factors help explain how efficiently investments are made, a big part of the efficiency is still affected by other things not included in the model. This means future research should look into more financial and non-financial factors as well.